The Effect of Gray Marketing on Brand Value from the Perspective of Customers: A Field Study on Users of International Sports Brands in Cairo Governorate - Abd El-Aal, Mohamed Hamdy Zaki (The Arab Journal of Administration, 2025)
The study aims to identify the impact of gray marketing dimensions (gray product, gray pricing, gray promotion, and gray distribution) on the value of the brand from the perspective of customers who use international sports brands in Cairo Governorate. To achieve this goal, the study followed the descriptive analytical approach, where the survey tool was relied upon to collect primary data, The researcher also relied on using the sampling method for all customers using international sports brands in Cairo Governorate, where (384) survey forms were distributed, of which (341) questionnaires were subjected to statistical treatment. Some modern administrative scientific literature in the field of study was viewed and reviewed through digital and paper libraries, and available Internet sites, and previous studies related to the field of study were also inferred to benefit from and build upon. The results of the study showed a statistically significant positive effect of gray marketing dimensions on brand value from the perspective of customers using international sports brands in Cairo Governorate. The study recommended the necessity of working to increase the degree of awareness of the brand among customers who use international sports brands in Cairo Governorate, to import products and trademarks through guaranteed and legitimate legal distribution channels. The study also recommended the need for companies that own trademarks to pay attention to relations with customers and be careful to increase the degree of their connection. And their loyalty to those brands.